Psychosis Crisis Associated with Thyrotoxicosis due to Graves’ Disease - Lilibet Urias-Uribe; Emmanuel Valdez-Solis; Claudia González-Milán; Claudia Ramírez-Rentería; Aldo Ferreira-Hermosillo (Case Reports in Psychiatry)
We present the case of a patient with previous psychiatric illness, acutely exacerbated by thyroid storm due to Graves’ disease, in whom treatment with antipsychotics induced catatonia. These associations are extremely rare and may be confused with Hashimoto’s encephalopathy, especially in the presence of anti-thyroid antibodies in cerebrospinal fluid. The treatment consists in the control of the triggering disease (in this case the resolution of the thyrotoxicosis) and the use of benzodiazepines. However, in some cases, the resolution of psychiatric symptoms is partial and may require the use of electroconvulsive therapy.